2019
DOI: 10.2147/ijn.s210315
|View full text |Cite
|
Sign up to set email alerts
|

<p>Nanoparticle-Mediated Drug Delivery Systems For The Treatment Of IBD: Current Perspectives</p>

Abstract: Inflammatory bowel disease (IBD), which mainly consists of Crohn's disease and ulcerative colitis, is a chronic and relapsing inflammatory condition of the gastrointestinal tract. The traditional treatment strategies relied on frequent administration of high dosages of medications, including antibiotics, non-steroidal anti-inflammatory drugs, biologics, and immunomodulators, with the goal of reducing inflammation. Some of these medications were effective in alleviating the early-stage inflammatory symptoms, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(55 citation statements)
references
References 132 publications
(144 reference statements)
0
55
0
Order By: Relevance
“…On the other hand, the poor water solubility and low bioavailability limited the clinical use of this polyphenol [23]. The application of nanosystems based on colon targeted drug delivery is receiving considerable attention for local treatment of UC since they can decrease drug loss in proximal intestine and thus increase drug concentration in the colon [34]. Conventional nanovesicles are scarcely used since they can suffer from gastric and enzymatic degradation, reducing the drug oral bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the poor water solubility and low bioavailability limited the clinical use of this polyphenol [23]. The application of nanosystems based on colon targeted drug delivery is receiving considerable attention for local treatment of UC since they can decrease drug loss in proximal intestine and thus increase drug concentration in the colon [34]. Conventional nanovesicles are scarcely used since they can suffer from gastric and enzymatic degradation, reducing the drug oral bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolation to humans remains to be explored. Nanosized drug carriers may also result in increased penetration in the mucus layer [ 104 , 105 , 106 ]. In addition to the reduced size, the type of nanomaterial and shape can also be modified depending on the clinical applications.…”
Section: Formulation Strategiesmentioning
confidence: 99%
“…A certain number of NP delivery systems have sought to target drugs to the inflamed intestine. Although several NP-based drugs have entered clinical trials for the treatment of IBD, most have failed due to premature drug release, weak targeting ability, and the high immune toxicity of some of the synthetic nanomaterials that have been used to fabricate the NPs [ 102 , 103 , 104 , 105 , 106 ]. Additionally, numerous in vitro and in vivo experiments have demonstrated that not only nanoscaled synthetic drugs, but also phytochemicals and macromolecules encapsulated in nanoparticles can be used for the treatment of IBD and IBD-associated colorectal cancer [ 51 , 107 , 108 ].…”
Section: Designed Nanoddssmentioning
confidence: 99%